Effects of logging roads on erosion and sedimentation. - Jusoff, Kamaruzaman; Nik Ab. Majid, Nik Muhamad; Ahmad, Desa (1986)
Logging roads are necessary for log transportation in the forest of most ASEAN countries, especially Malaysia. The status of logging roads and some of their selected soil physical properties are given. The effects of logging roads construction on erosion and sediment yield are discussed. Defects of the practice affecting the physical properties of soil leading to erosion and sedimentation can be minimized through skilfull manipulation of heavy log transportation machines, careful advanced planning and scund soil conservation measures taken at the right time and place.